Fully parallel methods for a class of linear partial differential-algebraic equations - Vu, Tien Dung (H. : ĐHQGHN, 2017)
This note deals with two fully parallel methods for solving linear partial diíĩerentialalgebraic equations (PDAEs) of the form: Aut + BAu = /(x , t) (1) where A is a singular, symmetric and nonnegative matrix, while B is a symmetric positive define matrix. The stability and convergence of proposed methods are discussed. Some numerical experiments on high-performance computers are also reported.